A continuing journey towards students' development: The essence of being a neophyte teacher - Malaque, Feliciano Valdez (Animo Repository, 2018)
This qualitative study focused on the lived experiences of neophyte teachers in their first three (3) years of teaching as they entered the community of practice in the context of Philippine Private Education. The theoretical framework of Wenger (1998) on Social Theory of Learning was used as a lens to illuminate and explore the experiences of neophyte teachers. The research employed the hermeneutic phenomenological method to explore the lived experiences of neophyte teachers in their continuing journey towards students development. Max van Manens (1997) hermeneutic phenomenology provided a detailed process used to conduct this form of research, primarily to uncover the essence of this phenomenon, which was to elicit lived experience through hermeneutic conversation.To uncover the nature of the lived experience of neophyte teachers in their continuing journey towards students development, four (4) participants, who successfully finished their three-year probationary teaching, were recruited who happened to finished their first three years of teaching from different private secondary schools in Luzon, PhilippinesThe participants lived experiences encompassed four phases of their continuing journey towards students development which depicted the essence of being a neophyte teacher. The four phases include: phase I: The pre-neophyte period or the vocation and call to teaching phase II: Carrying the sense of pre-service idealism to the context of real teaching phase III: Realization and making sense of the challenges of teaching and phase IV: Gradual stabilization coping with the challenges and growing in the teaching profession.The results in this study uncovered many insights that may be of great help to those who are supporting neophyte teachers during their pre-service formation and in-service orientation. Identifying and proper understanding of the neophytes need would be of help in improving their teaching capacities and boost their morals to stay in the teaching profession.